PELATIHAN PEMBUATAN PUPUK BOKASHI DI PONDOK PESANTREN RAUDHATUL MADINAH KOTA BATU - Anugrah Windy Mustikarini; Anugrah Windy Mustikarini; Achmad Sjaifullah; Arief Budiono; Zakijah Irfin (P3M Politeknik Negeri Malang, 2023)
Community service through various forms of activities (PPM) is a manifestation of the commitment of the Department of Chemical Engineering at the State Polytechnic of Malang in implementing the Tri Dharma of Higher Education. The purpose of this PPM is to help meet the training needs of the Raudhatul Madinah Islamic Boarding School in order to improve the skills of students. One of the trainings that can be done is training on making bokasi fertilizer by utilizing surrounding waste. Aspects of the problems resolved in this PPM Program are improving the ability, competence, and understanding of the target audience as well as the utilization of waste into higher value products. This PPM activity consists of several activities, including: 1) Assistance in making bokashi fertilizer, 2) Delivery of materials for making bokashi fertilizer. The results of the PPM showed an increase in participants' knowledge and skills in making bokashi fertilizer. Furthermore, several PPM achievements that have been achieved include: Articles published in national journals with ISSN, and publication of activities on social media.